(untitled) (CIPEEX, 2022)
INTRODUCTION: EVERY DAY CHILDREN ARE VICTIMS OF SEXUAL VIOLENCE, WHERE EPISODES OF ABUSE ARE OFTEN PRACTICED IN THE HOME ENVIRONMENT, BEING CARRIED OUT BY PEOPLE WHO HAVE THE DUTY TO ASSURE THEIR PROTECTION. CHILD SEXUAL VIOLENCE IS A RELEVANT PUBLIC HEALTH PROBLEM THAT AFFECTS ALL STRATA OF SOCIETY AND ITS HIGH INCIDENCE CAUSES PHYSICAL, SOCIAL AND COGNITIVE IMPAIRMENT FOR CHILDREN VICTIMS AND THIS PRACTICE IS RELATED TO COMPLEX AND MULTIFACTORIAL ISSUES, AMONG THEM, FACTORS PARENTAL, SOCIAL AND STRUCTURAL FACTORS, THUS CONSTITUTING PREDISPOSING, BUT NOT DETERMINANT, FACTORS FOR THE PRACTICE OF VIOLENCE (MINAYO, 2017). OBJECTIVES: GENERAL: IDENTIFY CHARACTERISTICS OF SUSPECTED AND / OR CONFIRMED CASES OF SEXUAL ABUSE AGAINST THE CHILD, SUCH AS THE PROFILE OF THE POSSIBLE PERPETRATOR OF AGGRESSION AND ASSOCIATED VARIABLES, THROUGH THE CASES OF COMPULSORY NOTIFICATION OF VIOLENCE, INSERTED IN THE INFORMATION SYSTEM AND NOTIFICATION OFFENSES (SINAN), FROM 2010 TO 2016, IN A MUNICIPALITY IN THE INTERIOR OF THE STATE OF GOIS. METHODOLOGY: THIS IS A CROSS-SECTIONAL, PROSPECTIVE, DESCRIPTIVE STUDY WITH A QUANTITATIVE APPROACH, BEING THE SAMPLE FOR CONVENIENCE. RESULTS AND DISCUSSION: THERE WERE 185 CASES OF NOTIFICATION OF SEXUAL VIOLENCE AGAINST THE CHILD. SEXUAL VIOLENCE WAS PREVALENT IN THE FEMALE SEX (69.72%), AND THE HOME ENVIRONMENT WAS THE PREDOMINANT PLACE FOR THE PRACTICE OF SEXUAL ABUSE (88.5%). PARENTS, CAREGIVERS, CAREGIVERS AND ACQUAINTANCES WERE THE MAIN PERPETRATORS OF SEXUAL ABUSE (80.54%). IN 46.6% OF REPORTED CASES, THE CHILD WAS THE VICTIM OF MORE THAN ONE TYPE OF ABUSE. FINAL CONSIDERATIONS: IN VIEW OF THE SIGNIFICANT FREQUENCY OF SEXUAL VIOLENCE PRACTICED AGAINST THE CHILD BY PEOPLE OF THEIR AFFECTIVE AND SOCIAL NUCLEUS AND THE LACK OF PROTECTION IN WHICH THE CHILD VICTIM OF SEXUAL ABUSE IS, IT IS VERIFIED THAT THE MORE VULNERABLE THE CHILD IS, IT MAY BE SUBJECTED TO TWO FORMS OF VIOLENCE. IN THE DOMESTIC CONTEXT, CHILD SEXUAL VIOLENCE IS LINKED NOT ONLY TO SOCIO-STRUCTURAL FACTORS, BUT TO ASYMMETRICAL PARENTAL RELATIONSHIPS RELATED TO THE SUBORDINATION OF THE ONE WHO HOLDS THE DOMINATION AND STRENGTH OVER THE MOST FRAGILE, WHERE THIS CYCLE IS NOT INTERRUPTED, THIS PRACTICE CAN BE REPRODUCED IN A MULTIGENERATIONAL CYCLICAL PROCESS. ALTHOUGH THERE ARE LAWS THAT ENSURE THE PROTECTION OF CHILDREN, IT IS IMPERATIVE TO THINK IN DIFFERENT WAYS THAT FOSTER EFFECTIVE ACTIONS AND STRATEGIES TO PREVENT AND COPE WITH THIS PHENOMENON.